Insights on the epigenetic mechanisms underlying pulmonary arterial hypertension - Luna,R.C.P. (2018)
Pulmonary arterial hypertension (PAH), characterized by localized increased arterial blood pressure in the lungs, is a slow developing long-term disease that can be fatal. PAH is characterized by inflammation, vascular tone imbalance, pathological pulmonary vascular remodeling, and right-sided heart failure. Current treatments for PAH are palliative and development of new therapies is necessary. Recent and relevant studies have demonstrated that epigenetic processes may exert key influences on the pathogenesis of PAH and may be promising therapeutic targets in the prevention and/or cure of this condition. The aim of the present mini-review is to summarize the occurrence of epigenetic-based mechanisms in the context of PAH physiopathology, focusing on the roles of DNA methylation, histone post-translational modifications and non-coding RNAs. We also discuss the potential of epigenetic-based therapies for PAH.